Energies beyond the state: anarchist political ecology and the liberation of nature - Mateer, Jennifer; Springer, Simon; Locret-Collet, Martin; Acker, Maleea (Rowman & Littlefield, 2022)
Introduction -- The political ecology of resource and energy management beyond the state / Jennifer Mateer, Simon Springer, and Martin Locret-Collet -- Panoptic geography: man and nature under surveillance / Sotiris Lycourghiotis and George Poulados -- Uranium: capitalism, colonialism, and ecology / Chris Colella -- Moving beyond borders: anarchist political ecology and environmental -- displacement / Nicolas Parent & Jirón Mariscal José Antonio de Sucre Questioning capitalistic power structures: a way to reconnect people with -- lands? / Simon Maraud and Etienne Delay -- When the wolf guards the sheep: confronting the industrial machine through -- green extractivism in Germany and Mexico / Alexander Dunlap and Andrea Brock -- Dismantling the dam hierarchies / Jennifer Mateer -- The conservation of anarchy: ethnographic reflections on forest policies and -- resource use / Philipp Zehmisch -- Blockading Hamburg: green syndicalism vs G20 / Ryan Thompson -- Rising above the thinking behind climate change: world ecology and -- workers' control / Ben Debney -- The soft hand of capital / Deric Shannon and Clara Perez-Medina.